Electrolyte design principles for low-temperature lithium-ion batteries - Yang Yang; Wuhai Yang; Huijun Yang; Haoshen Zhou (eScience, 2023)
Alongside the pursuit of high energy density and long service life, the urgent demand for low-temperature performance remains a long-standing challenge for a wide range of Li-ion battery applications, such as electric vehicles, portable electronics, large-scale grid systems, and special space/seabed/military purposes. Current Li-ion batteries suffer a major loss of capacity and power and fail to operate normally when the temperature decreases to −20 ​°C. This deterioration is mainly attributed to poor Li-ion transport in a bulk carbonated ester electrolyte and its derived solid–electrolyte interphase (SEI). In this mini-review discussing the limiting factors in the Li-ion diffusion process, we propose three basic requirements when formulating electrolytes for low-temperature Li-ion batteries: low melting point, poor Li+ affinity, and a favorable SEI. Then, we briefly review emerging progress, including liquefied gas electrolytes, weakly solvating electrolytes, and localized high-concentration electrolytes. The proposed novel electrolytes effectively improve the reaction kinetics via accelerating Li-ion diffusion in the bulk electrolyte and interphase. The final part of the paper addresses future challenges and offers perspectives on electrolyte designs for low-temperature Li-ion batteries.